Dampak Kekohesifan Dan Gaya Kepemimpinan terhadap Efektivitas Organisasi Pada PT.Perkebunan Nusantara IV (Persero) Medan - Bella, Winda (JaManKu: Jurnal Manajemen dan Kewirausahaan, 2025)
This study aims to determine the impact of cohesiveness and leadership style on organizational effectiveness at PT. Perkebunan Nusantara IV (Persero) Medan. The dependent variable in this study is Organizational Effectiveness, while the independent variable consists of Impact of Cohesiveness and Leadership Style. In this study, all the pupulation were used as the samples, namely 212 employees at PT. Perkebunan Nusantara IV (Persero) Medan. The research method used in this method is validity, reliability, classical assumptions, partial test (t), simultaneous test (F), and path analysis with the help of the SPSS 16 software program. The results of this study indicate that the cohesiveness variable has a positive and significant effect on Organizational Effectiveness of 0.000 and t count of 4.166 is greater than t table of 1.652. Leadership Style has a positive and significant effect on Organizational Effectiveness of 0.000 and t count of 8.072 is greater than t table of 1.652. The impact of Cohesiveness and Leadership Style are both positive and significant on Organizational Effectiveness of 0.000 and F counting to 91.709, greater than F table 3.04.